Implementasi Kebijakan Kesejahteraan Sosial Pada Adaptasi Sosial Mahasiswa Difabel dalam Proses Pembelajaran - Qorir Yunia Sari; Achmad Zainal Arifin; Rama Sanjaya; Wisnu Nugraha; Zulkipli Lessy (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Negeri Balikpapan., 2022)
This study focuses on the implementation of Social Welfare policies on social adaptation in the learning process of students with disabilities in the Sociology Study Program of UIN Sunan Kalijaga. Efforts to fulfill accessibility have been carried out by the Difabel Service Center of UIN Sunan Kalijaga to make the learning process easier. However, these efforts do not deny that there are still obstacles for students with disabilities in participating in the learning process. This study uses a qualitative method. Collecting data through observation, interviews, and documentation. The interviews involved 8 disabled students, 7 non-disabled students, and 4 lecturers. The results showed that there was an adaptation stage in the learning process of students with disabilities in the Sociology Study Program, namely 1) Honeymoon, students with disabilities felt happy when accepted at UIN Sunan Kalijaga, 2) Culture Shock, various obstacles appeared in the learning process, 3) Recovery, program students Sociology Studies with disabilities try to overcome obstacles and apply them continuously, 4) Adjustments, students with disabilities in the Sociology Study Program are getting used to the learning process at UIN Sunan Kalijaga.